Pengaruh Pemberian Ekstrak Buah Naga Merah (Hylocereus polyrhizus) Terhadap Gambaran Spermatogenesis Tikus Putih (Rattus norvegicus) Galur Wistar yang Diinduksi Pakan Tinggi Lemak - Cantika, Yara; Fauziah, Cut; Setyaningsih, Yuni (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2019)
Spermatogenesis can be affected by oxidative stress produced by the increasing of pro-inflammatory adipokines because of high fat diet.The spermatogenesis cells damaged can be prevented with natural substance such as red pitaya (Hylocereus polyrhizus). This study aims to analyze effect of Hylocereus polyrhizus extract on rat?s spermatogenesis cells number that induced by high fat diet. This study had used true-experiment design. 30 rats were divided into 5 groups. Groups 1 to 4 had done treatment for 52 days and group 5 treatment for 104 days. Group 1 Negative control (K1) administered with standard diet, group 2 Positive control (K2) had administered quail egg 10ml/KgBW, group 3 Experiment 1 (P1) had administered quail egg polyrhyzus  10ml/Kg BW and with simvastatin 0,72mg/day, group 4 Experiment 2 (P2) had administered quail egg 10ml/KgBW and wth Hylocereus polyrhizus extract 60mg/day in 52 days, and group 5 Experiment 3 (P3) had administered quail egg 10ml/KgBW and with Hylocereus polyrhizus extract 60mg/day in 104 days. Data were analyzed by One Way ANOVA and continued with Post Hoc Tukey?s HSD (P-Value=0,05) for 52 day groups. Group P1 and P2 showed repairing effect and increasing spermatocytes and spermatids (p.000<0,05) compared to group K2. Group P2 had more spermatids and spermatocytes than group P1 (p.000<0,05). Group P2 52 days? spermatid cells equalled to group P3 104 days (p.469>0,05). Hylocereus polyrhizus extract not only had mechanism like simvastatin but also contained antioxidant, and a long-term treatment had not proven bad effect to spermatogenesis cells.  Conclusion. Hylocereus polyrhizus extract 60mg/day can repair and increase spermatogenesis cells induced with high fat diet.